TELEVISION FOOD ADVERTISING AND ITS IMPACT ON THE EATING HABITS OF INDIAN CHILDREN IN MALAYSIA: A MIXED-METHODS STUDY - Raj SM, Suthen; Vijayan , Phirriyalatha (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates the impact of television food advertising (TFA) on the eating habits of Indian children in Malaysia, employing a mixed-methods approach. The research aims to understand how TFA influences food preferences within the Malaysian Indian community and the role of socio-demographic factors in shaping these behaviors. Quantitative data was collected through surveys administered to a sample of Malaysian Indian children, assessing their trust in food advertisements and its effect on their food choices. Complementary qualitative data was obtained through in-depth interviews with parents, providing insights into their perceptions of their children's food preferences and the influence of TFA. The findings indicate that while TFA has a moderate impact on children's purchasing behaviors, socio-demographic factors such as age, gender, and parental education also play a significant role. The study underscores the need for targeted interventions by policymakers to mitigate the adverse effects of food advertising on children's health and promote healthier dietary choices. This research contributes to the broader understanding of the role of television in shaping child nutrition and offers practical recommendations for stakeholders seeking to improve the dietary habits of Malaysian Indian children.